Media Pembelajaran Berbasis STEM Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Aprianti, Yesi Dian; Ayu, Hena Dian; Sundaygara, Chandra (Fakultas Sains dan Teknologi Universitas Kanjuruhan Malang, 2023)
The aim of this research is to produce STEM-based learning media in the form of learning videos that have been tested for feasibility , practicality and effectiveness to improve students' critical thinking. The research model used is ADDIE, namely: 1) initial needs analysis to determine student needs; 2) initial media design and creating research instruments; 3) video development using the Canva and Animeker applications , as well as validation by media, material and language experts; 4) small-scale limited trials on 30 class VIII students; 5) evaluation from users, namely students and subject teachers. The results of media, material and language expert data analysis state that STEM-based learning media is suitable for use. Based on the feasibility assessment from media experts, a score of 93.75% was obtained, material experts obtained a score of 82% and language experts obtained a score of 90% in the